Role of DACH1 on Proliferation, Invasion, and Apoptosis in Human Lung Adenocarcinoma Cells - Yu, Junjie; Jiang, Ping; Zhao, Ke; Chen, Zhiguo; Zuo, Tao; Chen, Baojun (Current Molecular Medicine, 2021)
Objective: To investigate DACH1 protein expression in lung cancer tissue and matched paracancerous tissue and explore its effect on proliferation, invasion, and apoptosis in human lung adenocarcinoma cells (HLACs). Methods: Tumor tissue and matched paracancerous tissue were collected from 46 patients with pathologically diagnosed lung cancer. RT-PCR was performed to detect DACH1 mRNA expression and immunohistochemistry to measured DACH1 protein expression. To determine the effect of DACH1 on lung cancer behavior, small interfering RNA (siRNA) was used to silence DACH1 expression in A549 cells. The impact on the proliferation of tumor cells was then observed by MTT assay, changes in the invasion of tumor cells were identified using transwell chamber assay, and the effects on apoptosis in the cell line were detected using flow cytometry. Results: The expression of DACH1 mRNA and DACH1 protein was significantly decreased in lung cancer tissue versus matched paracancerous control tissue. The silencing of DACH1 expression in A549 cells significantly enhanced cell proliferation, significantly increased cell invasion, and significantly reduced spontaneous apoptosis. Conclusion: DACH1 is downregulated in lung adenocarcinoma tissue. In vitro assessment shows that DACH1 functions as a tumor suppressor, suggesting its potential use as a new target for lung cancer treatment.
Keywords: proliferation